Genome distribution of differential homoeologue contributions to leaf gene expression in bread wheat. Issue 5 (7th October 2015) - Harper, Andrea L.; Trick, Martin; He, Zhesi; Clissold, Leah; Fellgett, Alison; Griffiths, Simon; Bancroft, Ian
Summary: Using a combination of de novo transcriptome assembly, a newly developed 9495‐marker transcriptome SNP genetic linkage map and comparative genomics approaches, we developed an ordered set of nonredundant transcripts for each of the subgenomes of hexaploid wheat: A (47 160 unigenes), B (59 663 unigenes) and D (40 588 unigenes). We used these as reference sequences against which to map Illumina mRNA‐Seq reads derived from young leaf tissue. Transcript abundance was quantified for each unigene. Using a three‐way reciprocal BLAST approach, 15 527 triplet sets of homoeologues (one from each genome) were identified. Differential expression ( P < 0.05) was identified for 5248 unigenes, with 2906 represented at greater abundance than their two homoeologues and 2342 represented at lower abundance than their two homoeologues. Analysis of gene ontology terms revealed no biases between homoeologues. There was no evidence of genomewide dominance effects, rather the more highly transcribed individual genes were distributed throughout all three genomes. Transcriptome display tile plot, a visualization approach based on CMYK colour space, was developed and used to assess the genome for regions of skewed homoeologue transcript abundance. Extensive striation was revealed, indicative of many small regions of genome dominance (transcripts of homoeologues from one genome more abundant than the others) and many larger regions of genome repression (transcripts of homoeologues from one genome less abundant than the others).